Effects of 25‐hydroxy‐cholecalciferol on the development of osteochondrosis in swine. (19th November 2012) - Sugiyama, Toshie; Kusuhara, Seiji; Chung, Thau Kiong; Yonekura, Hiroshi; Azem, Elisabeth; Hayakawa, Takehiko
Abstract The principal objective of this experiment was to evaluate the effect of 25‐hydroxy‐cholecalciferol (25‐OH‐D3) on the development of osteochondrosis in 6‐ to 110‐kg castrated male pigs. The growth rate and serum calcium and inorganic phosphate levels neither increased nor decreased in response to supplementation of 25‐OH‐D3. However, supplemental 25‐OH‐D3 significantly increased serum levels of 25‐OH‐D3 and 1α, 25‐hydroxy‐cholecalciferol without any influence on bone mineral density. The 25‐OH‐D3‐treated group had significant (P < 0.05) reduced incidence of osteochondrotic lesions compared to the control group as evidenced by macroscopically examining the articular cartilage of the distal humerus (32.4% vs. 59.3%) and distal femur (47.1% vs. 87.5%). Likewise, supplemental 25‐OH‐D3 significantly reduced osteochondrotic lesions over the control when histologically examining humerus (20.6% vs. 43.8%) and femur (52.9% vs. 87.5%). The results of this experiment suggested that 25‐OH‐D3 supplementation in pig diets had a tendency to promote normal endochondral ossification, inhibit osteochondrosis progression and possibly regenerate destroyed cartilage tissue.